2018
DOI: 10.1007/s10897-018-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Genetic Counseling Self‐Efficacy Scale (GCSES)

Abstract: This study describes the development of a self-efficacy scale that is specific to genetic counseling and based both on Bandura's self-efficacy theory (2006) and the Accreditation Council for Genetic Counseling practice-based competencies (2013). The phase 1 validation compared genetic counseling students (n = 20) and genetic counselors (n = 18). Nine items were removed from the scale at this point for lack of discrimination or redundancy. The phase 2 validation included a larger cohort of genetic counseling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 13 publications
1
32
1
Order By: Relevance
“…There were 15 incomplete responses not included in the analyses, leaving a total of 115 completed questionnaires for a response rate of 39.5%. Thirty‐five participants (27%) recalled taking the survey distributed by Caldwell et al (), while half of the participants ( n = 66) were unsure if they had completed the previous questionnaire. The current sample's demographics were not statistically different from the sample in the study by Caldwell et al () for age and sex (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 15 incomplete responses not included in the analyses, leaving a total of 115 completed questionnaires for a response rate of 39.5%. Thirty‐five participants (27%) recalled taking the survey distributed by Caldwell et al (), while half of the participants ( n = 66) were unsure if they had completed the previous questionnaire. The current sample's demographics were not statistically different from the sample in the study by Caldwell et al () for age and sex (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The target population for the study was the same cohort of students in their second year of training in a genetic counseling training program accredited by the ACGC that was surveyed in the studies by Caldwell et al (). The students were surveyed in the fall of 2016 in the Caldwell et al () study while data collection for the current study took place from April 2017 to May 2017, near the end of clinical training for this cohort.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations